Peningkatkan Kreativitas Guru-Guru di Tengah Pandemi Covid-19 - Arkadius Roga (Sekolah Tinggi Agama Katolik Negeri Pontianak, 2022)
Distance Teaching or Learning From Home is not the expectation of either the teachers or the students. The conditions caused by the spread of the Covid-19 virus make it uncomfortable for everyone, especially teachers and students. With such a situation, teachers still try to provide teaching materials to students with different media and teaching techniques than before. The virtual encounter made many students find it difficult to accept teaching which resulted in a decrease in their interest in learning. In this case, the creativity of the teachers is required so that students' interest in learning does not decrease and even is able to attract, so they can follow and understand what is given. Inevitably, teachers need to learn more in education management, public speaking, psychology, computers and websites that are needed during the teaching process. These things are not because teachers do not study during education, but because of the pandemic situation that makes the learning process no longer face-to-face but virtual. This is what makes teachers need to adapt to new things and new thinking and creativity. In this case, teachers, in particular, need to be familiar with the internet and computer learning process as access to virtual learning. There are many media websites and applications that are helpful and interesting in the learning process so that students are interested and increase their interest in learning.